Modern Trends in E-Commerce Development - Насирова Зульфия Худайбергановна (European Science Publishing, 2023)
At the present stage of its development, Internet technology as an important economic factor influences all aspects of our lives. For this reason, the development of modern e-commerce trends is leading to the growth of the global economy. The rapid growth of e-commerce in developed countries and greater attention to its technological aspects will become the basis for the development of the countries' economies.
Keywords: E-commerce, trend, economics, organization, effect, development, world, science, method, level, experience.